Serum Cystatin C as an Indicator of Renal Function and Mortality in Liver Transplant Recipients. Issue 7 (July 2015) - Allen, Alina M.; Kim, W. Ray; Larson, Joseph J.; Colby, Colin; Therneau, Terry M.; Rule, Andrew D.
Abstract : Background/Aims: Chronic kidney disease (CKD) is an important comorbidity after liver transplantation (LT); however, reliable tools with which to evaluate these patients are limited. In this work, we examine the extent to which the addition of serum cystatin C improves glomerular filtration rate (GFR) estimation and mortality prediction, in comparison to various GFR-estimating equations. Methods: The GFR was measured in LT recipients by iothalamate clearance. Concurrent serum cystatin C was assayed in banked serum samples. Performance of GFR-estimating equations with and without cystatin C, including the modification of diet in renal disease and CKD-epidemiology collaboration formulas was assessed. The proportional hazards regression analysis was performed to determine the association between serum cystatin C and mortality. Results: A total of 586 iothalamate results were obtained in 401 patients after a mean of 4 years after LT. When compared to measured GFR, the formula with both creatinine and cystatin C, namely, CKD-epidemiology cr-cys, outperformed those with either marker alone. Performance of creatinine-based models was similar to one another. Serum cystatin C, by itself or as a part of an estimated GFR, was a significant predictor of mortality. Conclusions: Serum cystatin C has an important role in enhancing accuracy of GFR estimation and predicting mortality in LT recipients. Abstract : The authors evaluate different measures and equations to measure renal function after liver transplantation. The addition of cystatin C to measures of renal function significantly improves functional estimates and correlates with mortality outcomes. Supplemental digital content is available in the text.